Aqueous Hydrofluoric Acid Catalyzed Facile Synthesis of 2, 3, 6‐Substituted Quinoxalines. (17th March 2014) - Chandra Shekhar, A.; Ravi Kumar, A.; Sathaiah, G.; Raju, K.; Srinivas, P. V. S. S.; Shanthan Rao, P.; Narsaiah, B.
<x xml:space="preserve">Abstract</x> A versatile synthetic route for the preparation of 2, 3, 6‐trisubstituted quinoxalines in excellent yield is developed from θ‐diamines and 1, 2‐dicarbonyl compounds in which aqueous hydrofluoric acid was employed as the medium and catalyst. Other salient features of this protocol include milder conditions, absence of coupling agents, and easy workup procedures.